2021
DOI: 10.3844/ajisp.2021.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Acute Effect of Tramadol Intoxication on Some Immunological Parameters

Abstract: Tramadol intoxication is rapidly on the increase in Nigeria with unestablished short-term and long-term effects. The study was aimed at elucidating the dose-dependent effect of acute or chronic tramadol intoxication on some immunological parameters using male rats (Rattus norvegicus). A total of fifty adult rats were used for the study as indicated by Mead's Resource Equation. The study consisted of acute and chronic categories of fifty adult rats randomly pair-divided into groups of six rats each. The acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The immunological status of the body upon exposure to acute or chronic tramadol intoxication or administration is still unclear [34] . Some of the studies posited that tramadol intoxication has significant effects on some immunological parameters, whereas others are of contrary opinion [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunological status of the body upon exposure to acute or chronic tramadol intoxication or administration is still unclear [34] . Some of the studies posited that tramadol intoxication has significant effects on some immunological parameters, whereas others are of contrary opinion [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The immunological status of the body upon exposure to acute or chronic tramadol intoxication or administration is still unclear [34] . Some of the studies posited that tramadol intoxication has significant effects on some immunological parameters, whereas others are of contrary opinion [34] . However, in this present study, the depletion in the percentage of viable neutrophils after incubation with tramadol (300 µg/ml, 3000 µg/ml and 30,000 µg/ml) (Figure 2) suggested that abuse of tramadol could also alter the phagocytic activity of the neutrophils and result in neutropenia.…”
Section: Discussionmentioning
confidence: 99%